2018
DOI: 10.3389/fchem.2018.00136
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual DFT Study of the Local Chemical Reactivity of the Colored BISARG Melanoidin and Its Protonated Derivative

Abstract: This computational study assessed eight fixed RSH (range-separated hybrid) density functionals that include CAM-B3LYP, LC-ωPBE, M11, MN12SX, N12SX, ωB97, ωB97X, and ωB97XD related to the Def2TZVP basis sets together with the SMD solvation model in the calculation the molecular structure and reactivity properties of the BISARG intermediate melanoidin pigment (5-(2-(E)-(Z)-5-[(2-furyl)methylidene]-3-(4-acetylamino-4-carboxybutyl)-2-imino-1,3-dihydroimidazol-4-ylideneamino(E)-4-[(2-furyl)methylidene]-5-oxo-1H-imi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 78 publications
2
49
0
Order By: Relevance
“…In the same way, as in our recent works on melanoidins [6][7][8][9][10], it has been found that the model chemistry formed by the connection between the MN12SX density functional and the Def2TZVP basis set is the best for justifying the fulfilling of the KID procedure for the dansylglycine molecule, both in the presence of water and dioxane. is, instead of presenting the comparison of the values of the orbital energies with the ionization potential I and the electron affinity A for different density functionals, we are showing the results for the global descriptors calculated with the MN12SX density functional in Table 1 comparing the values that arise from both solvents.…”
Section: Resultssupporting
confidence: 53%
See 3 more Smart Citations
“…In the same way, as in our recent works on melanoidins [6][7][8][9][10], it has been found that the model chemistry formed by the connection between the MN12SX density functional and the Def2TZVP basis set is the best for justifying the fulfilling of the KID procedure for the dansylglycine molecule, both in the presence of water and dioxane. is, instead of presenting the comparison of the values of the orbital energies with the ionization potential I and the electron affinity A for different density functionals, we are showing the results for the global descriptors calculated with the MN12SX density functional in Table 1 comparing the values that arise from both solvents.…”
Section: Resultssupporting
confidence: 53%
“…Following the lines of our previous work [6][7][8][9][10], the computational studies were performed with the Gaussian 09 [34] series of programs with density functional methods as implemented in the computational package. e basis set used in this work was Def2SVP for geometry optimization and frequencies, while Def2TZVP was considered for the calculation of the electronic properties [35,36].…”
Section: Settings and Computational Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Frau and Glossman-Mitnik, the evaluation of marine peptides and melanoidins in the generation of HOMO and LUMO energies is required in the verification of the levels of agreement with the estimated Koopmans' theorem based on the combination of the MN12SX density functional and the Def2TZVP basis set [22][23][24][25][26][27][28]. This justifies the application of the proposed KID (for Koopmans in DFT) technique.…”
Section: Calculation Of Global Reactivity Descriptorsmentioning
confidence: 99%